Linguistic representation of violence in judicial opinions in Malaysia - Norzanita Othman,; Nor Fariza Mohd Nor,; Noraini Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Violent behaviour is understood as being a social and unilateral action initiated by one party. It is social in nature as it occurs within an interpersonal context and unilateral per se because it involves action taken by one individual against the well-being of another. Judges use strategic discursive strategies to describe the accounts of the crime in their judicial decisions. This research aims to investigate the language used by judges to describe the accounts of rape in selected appellate judgments of sexual violence cases in Malaysia. Specifically, it aims to investigate the discursive strategies adopted by judges to reformulate the description of the crime. The findings revealed that violent, disapproving, sexual, and ambiguous terms were adopted. It was also revealed that the crime is often characterized as a non-coerced and mutually-consented behaviour rather than a criminal act. This results in minimizing the level of violence, the mitigation of offender’s responsibility, and the relegation of victim’s experience to the background. Another significant finding from this study is the issue of judges’ ‘interpretative repertoires’ in describing cases of sexual violence. We recommend for future studies to include a bigger sample size, as well as to study whether different rape categories namely acquaintance rape, incestuous rape, and stranger rape would reveal distinctive terms used for the respective rape types.